Terrorism and Education - Tinnes, Judith (Perspectives on terrorism, 2024)
This bibliography contains journal articles, book chapters, books, edited volumes, theses, grey literature, bibliographies and other resources on the multi-faceted relationship between terrorism and education. It covers a wide range of aspects (such as how education affects radicalisation processes, the impact of (counter-)terrorism on educational institutions, or the training of terrorist actors). The bibliography focuses on recent publications (up to April 2024) and should not be considered as exhaustive. The literature has been retrieved by manually browsing more than 200 core and periphery sources in the field of Terrorism Studies. Additionally, full-text and reference retrieval systems have been employed to broaden the search.